In vitro fermentation of mixed rumen microorganisms on molasses-based substrates - Abdullah, Norhani (Universiti Pertanian Malaysia, 1986)
A fermentor consisting of two compartments (called inner and outer) separated by a dialysis membrane was developed for studying the digestion pattern in vitro of rumen microorganisms of sheep fed a molasses-urea based diet. A bout 35 ml of strained rumen liquor withdrawn from Merino weathers adapted to a molasses-urea diet (100 g oaten chaff and molasses containing 3% urea and 0.135% mineral mix fed ad libitum) was used as the initial fermenting inoculum in the inner compartment. Molasses-urea substrate (8.333% molasses and 0.277% urea, w/v) prepared in artificial saliva was infused at 3 ml h-1 into the fermenting medium and artificial saliva at 30 ml h-1 into the outer compartment. Incubation was carried out in a specially constructed water bath maintained at 39°C and filled with CO2 gas. With these flow rates, pH of fermenting fluids was maintained within physiological range with volatile fatty acids (VFA) production at 30 - 40 μmole ml-1 h-1. Using the fermentor, the effect of partial substitution of tryptone for urea as a nitrogen source on rumen microorganisms adapted to a molasses-urea based diet was studied with infusion solution consisting of 8.333% molasses, 0.208% urea and 0.202% tryptone (w/v) prepared in artificial saliva. Factors related to cell yield studied were, VFA and ammonia (NH) productions, dry matter (DM) and CP yields. However, no positive effects of protein supplementation (when compared to molasses-urea substrate) were observed in VFA productions, DM and CP yields. Only NH 3 levels of fermentors infused with molasses-urea substrate were significantly higher (P<0.05) than protein supplemented fermentors.